CADASIL and CARASIL. (September 2014) - Tikka, Saara; Baumann, Marc; Siitonen, Maija; Pasanen, Petra; Pöyhönen, Minna; Myllykangas, Liisa; Viitanen, Matti; Fukutake, Toshio; Cognat, Emmanuel; Joutel, Anne; Kalimo, Hannu
Abstract CADASIL and CARASIL are hereditary small vessel diseases leading to vascular dementia. CADASIL commonly begins with migraine followed by minor strokes in mid‐adulthood. Dominantly inherited CADASIL is caused by mutations (n > 230) in NOTCH3 gene, which encodes Notch3 receptor expressed in vascular smooth muscle cells (VSMC). Notch3 extracellular domain (N3ECD) accumulates in arterial walls followed by VSMC degeneration and subsequent fibrosis and stenosis of arterioles, predominantly in cerebral white matter, where characteristic ischemic MRI changes and lacunar infarcts emerge. The likely pathogenesis of CADASIL is toxic gain of function related to mutation‐induced unpaired cysteine in N3ECD. Definite diagnosis is made by molecular genetics but is also possible by electron microscopic demonstration of pathognomonic granular osmiophilic material at VSMCs or by positive immunohistochemistry for N3ECD in dermal arteries. In rare, recessively inherited CARASIL the clinical picture and white matter changes are similar as in CADASIL, but cognitive decline begins earlier. In addition, gait disturbance, low back pain and alopecia are characteristic features. CARASIL is caused by mutations (presently n = 10) in high‐temperature requirement. A serine peptidase 1 (HTRA1) gene, which result in reduced function of HTRA1 as repressor of transforming growth factor‐β (TGF β) ‐signaling. Cerebral arteries show loss of VSMCs and marked hyalinosis, but not stenosis.